2017
DOI: 10.3747/co.24.3584
|View full text |Cite
|
Sign up to set email alerts
|

Women with Cancer in Low-Income Countries

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Being unemployed itself is a risk factor for having a low income, which is one of the major obstacles in the early detection of breast cancer. In addition, the cost of diagnostic procedures is a challenge in breast cancer prevention [9]. In the current study, the majority of the women in the cases group were unemployed, which can be a clear reason for some of them being in the low-income category.…”
Section: Discussionmentioning
confidence: 72%
“…Being unemployed itself is a risk factor for having a low income, which is one of the major obstacles in the early detection of breast cancer. In addition, the cost of diagnostic procedures is a challenge in breast cancer prevention [9]. In the current study, the majority of the women in the cases group were unemployed, which can be a clear reason for some of them being in the low-income category.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, the expenses of diagnostic procedures make breast cancer prevention difficult. 23 The majority of women who participated in the current study were unemployed, which might explain why the majority had family monthly incomes ranging between 5000 and 15,000 (51.4%), which are classified as moderate income. This research shows that 71% of Saudi women have poor knowledge regarding breast cancer warning signs, risk factors, screening programs, and BSE.…”
Section: Discussionmentioning
confidence: 91%
“…Being unemployed is a risk factor for having a low income, which is one of the main barriers to the early detection of breast cancer. In addition, the cost of diagnostic procedures is a problem in breast cancer prevention (20) . Thereby, we found that low SES, low level of education (illiterate and read and write primary, secondary, and preparatory school levels), and unemployment were found to be risk factors for developing breast cancer in our study.…”
Section: Resultsmentioning
confidence: 99%